Constitutional Relations Between The President, The House Of Representatives, And The Regional Representative Boards In Lawmaking After The Amendment Of The 1945 Constitution - Fatoni, A.; Rahman, Arif (Universitas Serang Raya, 2024)
Amendments to the 1945 Constitution shifted legislation authority from the President to the House of Representatives. However, the strengthening of the House of Representatives into a 'super parliament' does not necessarily give it absolute power in lawmaking. Every draft bill, whether originating from the House of Representatives or the President, must be discussed and approved together to be enacted. From the outset, the 1945 Constitution did not apply the pure doctrine of Montesquieu's trias politica. The separation of powers is understood in the sense of 'distribution of power', making the House of Representatives and the President both have legislation authority. The bicameral parliament system allows the Regional Representative Boards to be able to submit draft bills relating to autonomous authority and participate in joint discussions. The participation of the executive in the discussion of the draft bill with the legislative is because the executive holds the function of implementing the law. Thus, the draft bill must be discussed together to obtain the approval of both institutions. Once approved, each draft bill will then be approved by the President.